Essential roles of Lon protease in the morpho-physiological traits of the rice pathogen Burkholderia glumae. - Eunhye Goo (Public Library of Science (PLoS), 2021)
The highly conserved ATP-dependent Lon protease plays important roles in diverse biological processes. The lon gene is usually nonessential for viability; however, lon mutants of several bacterial species, although viable, exhibit cellular defects. Here, we show that a lack of Lon protease causes pleiotropic effects in the rice pathogen Burkholderia glumae. The null mutation of lon produced three colony types, big (BLONB), normal (BLONN), and small (BLONS), in Luria-Bertani (LB) medium. Colonies of the BLONB and BLONN types were re-segregated upon subculture, while those of the BLONS type were too small to manipulate. The BLONN type was chosen for further studies, as only this type was fully genetically complemented. BLONN-type cells did not reach the maximum growth capacity, and their population decreased drastically after the stationary phase in LB medium. BLONN-type cells were defective in the biosynthesis of quorum sensing (QS) signals and exhibited reduced oxalate biosynthetic activity, causing environmental alkaline toxicity and population collapse. Addition of excessive N-octanoyl-homoserine lactone (C8-HSL) to BLONN-type cell cultures did not fully restore oxalate biosynthesis, suggesting that the decrease in oxalate biosynthesis in BLONN-type cells was not due to insufficient C8-HSL. Co-expression of lon and tofR in Escherichia coli suggested that Lon negatively affects the TofR level in a C8-HSL-dependent manner. Lon protease interacted with the oxalate biosynthetic enzymes, ObcA and ObcB, indicating potential roles for the oxalate biosynthetic activity. These results suggest that Lon protease influences colony morphology, growth, QS system, and oxalate biosynthesis in B. glumae.